Assessing instructional effects of proficiency-level EFL pronunciation teaching under a connected speech-based approach - Euler, Sasha S. (Studies in Second Language Learning and Teaching, 2014)
This article discusses the assessment of pronunciation instruction under a new approach to pronunciation teaching centered on the role of connected speech in the prosodic system of English. It also offers a detailed discussion of various empirical problems in teaching-oriented L2 pronunciation research and suggests ways of addressing them in intervention studies. A new explanatory sequential mixed-methods design was developed for this study, which was used to assess 10 advanced EFL learners in Germany before and after 13 weeks of instruction. The results revealed co-occurring developments in learners’ use of prosody and connected speech in line with the rationale of the approach. The findings lead to various implications for language teaching and assessment. For future research, ways are suggested to increase the validity and predictiveness of L2 pronunciation research from both empirical and pedagogical perspectives.